2022
DOI: 10.1038/s41467-022-35078-8
|View full text |Cite
|
Sign up to set email alerts
|

Rolling microswarms along acoustic virtual walls

Abstract: Rolling is a ubiquitous transport mode utilized by living organisms and engineered systems. However, rolling at the microscale has been constrained by the requirement of a physical boundary to break the spatial homogeneity of surrounding mediums, which limits its prospects for navigation to locations with no boundaries. Here, in the absence of real boundaries, we show that microswarms can execute rolling along virtual walls in liquids, impelled by a combination of magnetic and acoustic fields. A rotational mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…Because of the wall effect, i.e., the viscosity near a solid boundary is larger than that far from it, the swarm could roll along the wall. Moreover, using acoustic fields, virtual walls were created for guiding the motion of the rotating swarm . Without the virtual walls, the swarms rotated in the acoustic pressure nodes without making translation [Figure G­(i)].…”
Section: Acoustic Field-guided Micro/nanorobotic Swarmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the wall effect, i.e., the viscosity near a solid boundary is larger than that far from it, the swarm could roll along the wall. Moreover, using acoustic fields, virtual walls were created for guiding the motion of the rotating swarm . Without the virtual walls, the swarms rotated in the acoustic pressure nodes without making translation [Figure G­(i)].…”
Section: Acoustic Field-guided Micro/nanorobotic Swarmsmentioning
confidence: 99%
“…Moreover, using acoustic fields, virtual walls were created for guiding the motion of the rotating swarm. 247 Without the virtual walls, the swarms rotated in the acoustic pressure nodes without making translation [Figure 5G(i)]. Once the virtual walls were generated, the swarms rolled and realized translation [Figure 5G(ii)].…”
Section: Acoustic Field-guided Micro/nanorobotic Swarmsmentioning
confidence: 99%
“…further demonstrated a fundamentally new mechanism of rolling motion, i.e., rolling without dependence on real physical boundaries. [ 26 ] Dayton et al. utilized the acoustic radiation forces to concentrate microbubble contrast agents near a vessel wall in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Zhang et al further demonstrated a fundamentally new mechanism of rolling motion, i.e., rolling without dependence on real physical boundaries. [26] Dayton et al utilized the acoustic radiation forces to concentrate microbubble contrast agents near a vessel wall in vivo. [41] Finally, an acoustic vortex beam and standing wavefield have been applied to manipulate micrometer-and millimeter-sized particles in vivo using phased-array and acoustic standing wavefield approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation